Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

Multi-mycotoxin contamination, dietary exposure and health risk assessment of maize consumed in Niger State, Nigeria - Fatimah Omolola Badmos; Maimuna Abdullahi Habib; Victor Tope Oyetunji; Achi Dabara; Hadiza Kudu Muhammad; Abdullahi Abdulkadir; Susan Salubuyi; Daniel Ojochenemi Apeh; Maurice Monjerezi; Limbikani Matumba; Mulunda Mwanza; Hussaini Anthony Makun (Mycotoxin Research, 2026)

Phosphorene based nano-sensors for mycotoxins in food products: a review - Bilal Afzal; Nuzhat Jamil; Khadija Gull; Muhammad Yasir; Qudsia Kanwal; Toheed Ahmed; Attaullah Bukhari (Mycotoxin Research, 2026)

Aflatoxin surveillance in Punjab’s dairy sector: feed and milk contamination - Naveed Akbar; Farhan Saeed; Muhammad Atif Randhawa; Sanaullah Iqbal; Asif Meraj; Abhayveer Singh; Bushra Niaz; T. Krithiga; Rajashree Panigrahi; Amara Rasheed; Zunaira Basharat; Muhammad Afzaal; et al. (Mycotoxin Research, 2026)

Relation of aflatoxin M1 contamination with milk production, health, and reproductive performance of commercial dairy herds in Punjab, Pakistan - Talat Naseer Pasha; Muhammad Uzair Akhtar; Muhammad Naveed ul Haque (Mycotoxin Research, 2026)

Aflatoxin B1-associated oxidative stress along with toxicopathological and immunological alterations is efficiently counteracted by dietary supplementation of distillery yeast sludge in broilers - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Muhammad Kashif Saleemi; Halis Oguz; Shafia Tehseen Gul; Rao Zahid Abbas; Ashiq Ali; Sheraz Ahmad Bhatti (Mycotoxin Research, 2024)

Mycotoxin contamination in the Arab world: Highlighting the main knowledge gaps and the current legislation - Mohamed F. Abdallah; Muhammad Gado; Doha Abdelsadek; Fatma Zahran; Nada Nabil El-Salhey; Ohaila Mehrez; Sara Abdel-Hay; Sahar M. Mohamed; Karl De Ruyck; Shupeng Yang; Gerard Bryan Gonzales; Elisabeth Varga (Mycotoxin Research, 2024)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

Mycotoxin levels and characterization of natural anti-fungal phytochemicals in pearl millet (Pennisetum glaucum) from Nigeria’s six agroecological zones - Hadiza Kudu Muhammad; Hadiza Lami Muhammad; Patrick Berka Njobeh; Maurice Monjerezi; Limbikani Matumba; Hussaini Anthony Makun (Mycotoxin Research, 2022)

Aflatoxin contamination in different fractions of rice from Pakistan and estimation of dietary intakes - Shahzad Z. Iqbal; Muhammad R. Asi; Agustin Ariño; Noreen Akram; Muhammad Zuber (Mycotoxin Research, 2012)

Comparing aflatoxin contamination in chilies from Punjab, Pakistan produced in summer and winter - Shahzad Zafar Iqbal; R. Russell M. Paterson; Ijaz A. Bhatti; Muhammad R. Asi (Mycotoxin Research, 2011)

Aflatoxin B1 in chilies from the Punjab region, Pakistan - Shahzad Z. Iqbal; R. Russell M. Paterson; Ijaz A. Bhatti; Muhammad R. Asi; Munir A. Sheikh; Haq N. Bhatti (Mycotoxin Research, 2010)

Proteome analysis of Aspergillus ochraceus - Muhammad Rizwan; Ingrid Miller; Fareeha Tasneem; Josef Böhm; Manfred Gemeiner; Ebrahim Razzazi-Fazeli (Mycotoxin Research, 2010)